Vaping and Orthopaedic Surgery: A Review of Current Knowledge. Issue 1 (January 2019) - Amaro, Emilie J.; Shepard, Nicholas; Moss, Lewis; Karamitopoulos, Mara; Lajam, Claudette
Abstract : Smoking cessation improves surgical outcomes in orthopaedic patients. Electronic cigarettes (ECs) have been studied as a smoking-cessation tool but are now being used by previous nonsmokers. ECs may diminish the hazards of conventional tobacco use and serve as a nicotine-delivery device. EC vapor is associated with cytotoxicity, pro-inflammatory effects, and decreased microbial defense, which may increase perioperative risk for patients undergoing surgery. EC use in the adolescent population is growing and may pose unique health hazards and operative concerns in an at-risk population. EC use is difficult to study clinically as most electronic health records do not capture use and because many products with different ingredients exist. Future clinical trials are needed to evaluate the perioperative risks of ECs.